National Health Interview Survey, 1991: Drug and Alcohol Use Supplement ([Verlag nicht ermittelbar], 1993)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1991 [ICPSR 6049]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. Variables unique to this supplement include respondents' use of alcohol, sedatives, tranquilizers, painkillers, inhalants, stimulants, heroin, hallucinogens, marijuana, and cocaine. Respondents were also asked if they ever used a controlled substance, how often they used it, when they last used it, and at what age they first used it. Questions about personal and legal problems due to drug and/or alcohol use were asked as well. In addition, respondents were queried about activities performed while under the influence of drugs and/or alcohol, and if they had tried to cut down on the use of these substances.